2022
DOI: 10.1039/d2ay00041e
|View full text |Cite
|
Sign up to set email alerts
|

Determination of lentiviral titer by surface enhanced Raman scattering

Abstract: Lentiviruses are commonly used to deliver genetic code into host cells for biomedical applications, such as gene therapy, pharmaceuticals, and vaccine development. Knowing the infectious titer of these virus particles...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Together, the demonstration of the E-NoM platform for clinical sample screening that achieved the highly specific, sensitive, and simultaneous measurement of multiviral antigens indicated its potential for future clinical use. The progression from high analytical performance into clinical sample validation on a large patient cohort further distinguished this E-NoM platform from previous reports. …”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Together, the demonstration of the E-NoM platform for clinical sample screening that achieved the highly specific, sensitive, and simultaneous measurement of multiviral antigens indicated its potential for future clinical use. The progression from high analytical performance into clinical sample validation on a large patient cohort further distinguished this E-NoM platform from previous reports. …”
Section: Resultsmentioning
confidence: 79%
“…Different from the previous SERS works for virus detection, this E-NoM platform integrated the highly active anisotropic core–shell nanostructures, the electrohydrodynamic-driven fluid flow, and the NoM configuration for enabling the sensitive signal readout without the reliance on enzymatic amplification, sample filtration, and sophisticated statistical analysis. …”
Section: Resultsmentioning
confidence: 99%
“…Prior work has shown that it is possible to detect lentiviruses of similar size to the polystyrene beads using Silmeco substrates. 37 The compatibility between the 3D printed device and various solvents was further studied to determine which types of samples could be analyzed with this device. The experimental details for this experiment are in the ESI.…”
Section: Resultsmentioning
confidence: 99%
“…A previously reported homebuilt spectrometer was used to collect Raman spectra. 34 The spectrometer was equipped with a 785 nm laser (Oxxius). The laser was focused onto the samples through a 40× water immersion objective (numerical aperture (NA) = 0.8, Olympus), and the Raman scattering was collected through this same objective before being directed to an Isoplane SCT-320 spectrograph with a ProEM 1600 2 eXcelon3 charge-coupled device detector (Princeton Instruments).…”
Section: Methodsmentioning
confidence: 99%
“…The substrates were placed into a small petri dish with 3 mL of a 5 mM ethanolic solution of MBA to soak for at least 18 h. The substrates were then removed and rinsed with 3 mL of ethanol and ultrapure water before placing the substrates into a three-dimensional (3D)-printed flow cell. 34…”
Section: Substrate Functionalizationmentioning
confidence: 99%